2021
DOI: 10.3390/journalmedia2020015
|View full text |Cite
|
Sign up to set email alerts
|

Audience Views on Professional Norms of Journalism. A Media Repertoire Approach

Abstract: Despite several studies showing discrepancies between audience expectations of journalism and journalists’ professional norms, what remains largely unknown is the audience view on the adherence of journalism to these seemingly essential professional norms. Recent research mainly focused on analysing audience expectations within the context of specific cases. Moreover, these studies rarely take into consideration characteristics that might shape people’s views on journalism such as political ideology. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In previous studies, this diversity has been identified and described as the variety of devices and types of content that users engage in Dvir-Gvirsman (2020); Edgerly et al (2018); Kim (2016); Truyens and Picone (2021), or the combination of “highbrow” and “lowbrow” forms of content (Vandenplas and Picone 2021, 2023), for example in the form of quality and tabloid newspapers. While this fits within Hasebrink et al′s definition of diversity as an indicator of “the relations between the components of the repertoire” (Hasebrink and Domeyer 2012, 760), itself one of the central propositions of the repertoire approach (Hasebrink and Domeyer 2012, 759), I argue that these operationalizations have not yet managed to dig into the theoretical implications that the relationality of media repertoire components holds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In previous studies, this diversity has been identified and described as the variety of devices and types of content that users engage in Dvir-Gvirsman (2020); Edgerly et al (2018); Kim (2016); Truyens and Picone (2021), or the combination of “highbrow” and “lowbrow” forms of content (Vandenplas and Picone 2021, 2023), for example in the form of quality and tabloid newspapers. While this fits within Hasebrink et al′s definition of diversity as an indicator of “the relations between the components of the repertoire” (Hasebrink and Domeyer 2012, 760), itself one of the central propositions of the repertoire approach (Hasebrink and Domeyer 2012, 759), I argue that these operationalizations have not yet managed to dig into the theoretical implications that the relationality of media repertoire components holds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The number of news avoiders—people “who consume relatively little news, spend almost no time watching cable TV news channels, and avoid news magazines and news websites entirely” (Truyens and Picone, 2021: 265)—has risen across the world (Newman et al, 2021). A large number tends to be women; and there are several reasons for this.…”
Section: Gender Norms In News Avoidancementioning
confidence: 99%
“…News also provides social contact that helps us build status and associations with others (Berelson, 2004). Women’s disengagement with news can also compound mistrust: News avoiders are more likely to distrust the media and perceive media organizations as corrupt (Truyens and Picone, 2021). When public trust in journalism erodes, democracy is threatened (Schudson, 2002).…”
mentioning
confidence: 99%
“…The different views are often centred on the questions on normative media functions or what Gil de Zuniga and Hinsley (2013, p. 933) have referred to as 'good journalism traits'. Although formulations vary a little, these functions or traits, are remarkably alike from study to study and most often include the following: being objective/neutral, being a watchdog, being unbiased/neutral, being accurate, getting information to the public quickly, providing analysis of current affairs, being entertaining, being helpful to citizens in their everyday life, and so on (see, e.g., Gil de Zuniga & Hinsley, 2013;Tandoc & Duffey, 2016;Fawzi & Mothes, 2020;Riedel & Ebert, 2020;Truyens & Picone, 2021).…”
Section: Public Perceptions Of Journalismmentioning
confidence: 99%
“…But what constitutes 'good' journalism in the first place? Recent studies have shown that most research on journalism quality or adherence to journalistic professional norms is based on journalism's production processes or texts rather than the public's perceptions of or expectations of how journalism function (Meijer & Kormelink, 2019;Truyens & Picone, 2021). Karlsson andClearwall (2019, p. 1184) have argued that citizens' opinions are remarkably absent in most studies on 'good' or 'better' journalism.…”
Section: Introductionmentioning
confidence: 99%